Evaluation of Understanding of Clean Living Behavior in Diarrhea Prevention Efforts in Elementary School Students - Adnan, Yudi; Firda, Nur Faiqah; Maharani, Zaskia; Khayani, Nur Annisa; Pratiwi, Indah Putri (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2024)
Diarrhea remains a public health problem in Indonesia due to its high morbidity and mortality. The World Health Organization (WHO) reports that 100,000 Indonesian children die from diarrhea each year. Therefore, community service is very important to improve knowledge about hand washing behavior in school children. The purpose of this service is to evaluate knowledge about PHBS among elementary school students as an effort to prevent diarrhea. The targets were 33 students of Elementary Scholl (SD) of Inpres Kanreapia in Balanglohe Hamlet, Tombolopao District. This service method uses a combination of material delivery with PowerPoint, poster installation, and hand washing practice. Evaluation of counseling was carried out using post-test I and post-test II questionnaires to measure knowledge after 8 months of counseling, which was analyzed using the Friedman test. The results of statistical analysis showed a significant value of 0.050 (p>0.05), indicating that there was no statistically significant difference in knowledge regarding diarrhea prevention counseling with PHBS between the period before and after 8 months of counseling. Suggestions given during the implementation of the program have been implemented by SD Inpres Kanreapia, such as the provision of hand washing stations.